A survey of radiation dose to patients and operators during radiofrequency ablation using computed tomography - A., Saidatul; C. A., Azlan; M. S. A., Megat Amin; B. J. J., Abdullah; K. H., Ng (University of Malaya, 2010)
Link to publisher's homepage at http://www.biij.org/